Analisis Kestabilan Transien Akibat Penambahan Generator di Pabrik Gula - Duanaputri, Rohmanita; Muhammad Fahmi Hakim; Reyhan Aulia Rachman; Nuha Nadhiroh (Politeknik Negeri Malang, 2023)
The Assembagoes sugar factory has a production capacity of 3000 TCD and was revitalized in 2015, increasing the capacity to 6000 TCD. With the increase in production capacity, the supply of electrical energy, which had previously only come from one generator unit, was supplemented with one new 13 MW generator unit, increasing the total generation capacity to 23 MW. With this addition, the operation pattern of the electrical system changes, and the problem of system stability becomes one of the primary concerns that must be analyzed with improvements to the Assembaggoes sugar factory's electrical system. The goal of this research is to determine the system's frequency and voltage response when a brief stability disturbance occurs.